Enhanced heat transfer in a solar air heater with double-flow configuration by electrohydrodynamic technique - Nat Kasayapanand (2018)
Thermal characteristics of laminar forced convection inside solar flat-plate air heaters with double-flow configuration using the electrohydrodynamic technique are examined numerically. The electric field is generated by the wire electrodes with different arrangements charged with DC high voltage ranging from 7.5 to 17.5 kV. The numerical modeling of computational fluid dynamics includes the interactions between the electric field, flow field, and temperature field. It is found that the enhancement of heat transfer in the presence of the electric field increases in relation with the supplied voltage but decreases when the Reynolds number is augmented. The heat transfer enhancement is also depended on the total heat flux at an absorbing plate, the number of electrodes, and the channel geometry. © 2006 by Begell House, Inc.